2011
DOI: 10.1063/1.3658824
|View full text |Cite
|
Sign up to set email alerts
|

Ice particles trapped by temperature gradients at mbar pressure

Abstract: In laboratory experiments we observe that ice particles (≤ 100 µm) entrained in a low pressure atmosphere (∼ 1 mbar) get trapped by temperature gradients between three reservoirs at different tempertature. Confining elements are a peltier element at 250 K (bottom), a liquid nitrogen reservoir at 77 K (top) and the surrounding vacuum chamber at 293 K. Particle levitation and trapping is modeled by an interplay of thermophoresis, photophoresis and gravity. A number of ice particles are trapped simultaneously in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…As already discussed by Krauss et al (2007), levitating particles (in their case dust particles) tend to rotate. The same has been observed for the levitating ice particles in the experiment by Kelling et al (2011). Therefore, we here use the above‐mentioned trapping technique to perform a detailed study of the rotation of levitating ice particles which are under the influence of photophoresis, thermophoresis and gravity.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…As already discussed by Krauss et al (2007), levitating particles (in their case dust particles) tend to rotate. The same has been observed for the levitating ice particles in the experiment by Kelling et al (2011). Therefore, we here use the above‐mentioned trapping technique to perform a detailed study of the rotation of levitating ice particles which are under the influence of photophoresis, thermophoresis and gravity.…”
Section: Introductionsupporting
confidence: 55%
“…Therefore, it would be favourable if free particles were observed and manipulated in laboratory experiments. Fortunately, a technique to do so was recently developed by Kelling, Wurm & Dürmann (2011). In their work, they show that micron‐sized water ice particles levitate under the Earth’s gravity, trapped in stable positions by photophoresis and thermophoresis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prove this van Eymeren & Wurm (2012) carried out a detailed study of particle rotation. In their setup particles were levitated by means of thermophoresis and photophoresis (Kelling et al 2011). van Eymeren & Wurm (2012 found that at least more than 95% of all particles rotate around the vertical direction which coincides with the direction of illumination.…”
Section: Caveatsmentioning
confidence: 99%
“…A technique to trap particles was recently developed by Kelling et al (2011). They show that micron-sized irregular-shaped water-ice particles levitate under the Earth's gravity due to photophoresis and thermophoresis.…”
Section: Introductionmentioning
confidence: 99%